Wound Healing Activity of Nanoemulgel Containing Artocarpus lakoocha Roxb. Extract on Burns Model in Rat - Tanjung, Siti Aisyah; Silalahi, Jansen; Reveny, Julia (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The content of secondary metabolites in mobe leaves has the potential to be used in wound healing. Artocarpine, one of the secondary metabolites found in mobe leaves, is reported to affect the expression of transforming growth factor-beta (TGF-β) protein, thereby increasing fibroblast cell proliferation and accelerating the wound healing process. AIM: This study aims to determine the wound healing activity of nanoemulgel-containing ethanol extract of mobe leaves. MATERIALS AND METHODS: The method used in this study was experimental using chemicals ethanol 96%, Carbopol 940, PEG 400, Propylene glycol, Methyl Paraben, Propyl Paraben, Triethanolamine, Aqua Destillata. Mode leaves which were taken purposively were then formulated in nanoemulgel preparations which were tested for wound healing in male rats. The nanoemulgel preparation was then evaluated which included homogeneity, emulsion type, pH, viscosity, dispersion, and measurement of the nanoemulgel globules of mobe leaf extract, stability of the nanoemulgel preparation. Tests for the healing effect of burns were carried out on male rats for 14 days. RESULTS: Mobe leaves ethanol extract can be formulated into nanoemulgel dosage forms. This study showed wound healing activity of nanoemulgels with concentration variation of mobe leaves ethanol extract. The percentage of wound diameter reducing and fibroblast cells value were showed to increase and significantly different to negative control (p < 0.05) in 14 days. Platelet-derived growth factor (PDGF)-BB and TGF-β1 immunoexpression evaluation result showed significantly different to Blanko group (p < 0.05) in 14-day observation. CONCLUSION: From this study, nanoemulgel mobe can stimulate more fibroblast cell proliferation by greatly expressing TGF-β1 and PDGF BB in burn wounds.